1987
DOI: 10.1161/01.str.18.1.217
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood ketone and glucagon levels cannot account for 1,3-butanediol induced cerebral protection in the Levine rat.

Abstract: 1,3-Butanediol is an ethanol dimer that induces systemic ketosis. It has previously been shown to increase hypoxic survival time and reduce neurologic deficit in several experimental preparations. The aim of this study was to determine if the mechanism of 1,3-butanediol-induced cerebral protection was elevation of blood ketone levels, blood glucagon levels, or both. Blood /3-hydroxybutyrate levels, glucagon levels, or both produced by a previously reported protective dose of 1,3-butanediol (47 mmol/kg) were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…23 However, our results indicate that ethanol, unlike butanediol, does not prevent the development of edema secondary to embolization and are consistent with those of other studies that reported no beneficial effect of ethanol in various models of brain injury. Pretreatment with 47 mmol/kg ethanol, unlike pretreatment with butanediol, did not increase survival time in the Levine rat model, 24 and high doses of ethanol (87 mmol/kg) potentiated traumatic spinal cord and cerebral hemisphere damage in cats. 25 -26 Ethanol (100 mmol/kg) had no significant effect on the concentrations of cerebral energy metabolites in intact or ischemic rats, 27 which contrasts with the metabolic effects of butanediol that we report.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…23 However, our results indicate that ethanol, unlike butanediol, does not prevent the development of edema secondary to embolization and are consistent with those of other studies that reported no beneficial effect of ethanol in various models of brain injury. Pretreatment with 47 mmol/kg ethanol, unlike pretreatment with butanediol, did not increase survival time in the Levine rat model, 24 and high doses of ethanol (87 mmol/kg) potentiated traumatic spinal cord and cerebral hemisphere damage in cats. 25 -26 Ethanol (100 mmol/kg) had no significant effect on the concentrations of cerebral energy metabolites in intact or ischemic rats, 27 which contrasts with the metabolic effects of butanediol that we report.…”
mentioning
confidence: 79%
“…36 - 37 Intracerebral production of /3-hydroxybutyrate seems to be an important factor in the protective action of butanediol. Lundy et al 24 reported that acute elevation of blood ketone levels of /3-hydroxybutyrate infusion was not sufficient to provide cerebral protection in the Levine rat model.…”
mentioning
confidence: 99%
“…As mentioned earlier, immediate postischemic infusion of acetyl‐ L ‐carnitine is neuroprotective, possibly by providing alternative oxidative fuel in the presence of reduced conversion of pyruvate to acetyl CoA. Other researchers have demonstrated neuroprotection by administration of ketone bodies, e.g., β‐hydroxybutyrate, in animal models of ischemia, trauma, and Parkinson's disease (Lundy et al, 1984, 1987; Marie et al, 1987; Sims and Heward, 1994; Kashiwaya et al, 2000; Ottani et al, 2003; Tieu et al, 2003; Yosunkaya et al, 2004). Although the mechanism of neuroprotection by ketone bodies is not characterized, they similarly bypass the PDHC reaction and provide fuel to the TCA cycle.…”
Section: Potential Therapeutic Interventionsmentioning
confidence: 93%
“…22 However, motor performance was not improved by BD following severe forebrain ischemia, afford cerebral protection. 24 In addition, other known effects of BD such as changes in blood glucagon, insulin, and glucose levels were not found to correlate with the protective effect. 24 So far, the mechanisms by which BD exerts its protective effect remain unknown.…”
Section: Ischemic Brain Damage Is Not Ameliorated By 13-butanediol Imentioning
confidence: 93%
“…24 In addition, other known effects of BD such as changes in blood glucagon, insulin, and glucose levels were not found to correlate with the protective effect. 24 So far, the mechanisms by which BD exerts its protective effect remain unknown. Nevertheless, Marie et al 25 showed that BD ameliorates ischemic brain damage, accompanied by a reduced brain lactate accumulation and a reduced diminution of high-energy metabolite concentrations after transient forebrain ischemia in rats.…”
Section: Ischemic Brain Damage Is Not Ameliorated By 13-butanediol Imentioning
confidence: 93%